2011
DOI: 10.1128/jb.06384-11
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Degradation of tert-Amyl Alcohol Proceeds via Hemiterpene 2-Methyl-3-Buten-2-ol by Employing the Tertiary Alcohol Desaturase Function of the Rieske Nonheme Mononuclear Iron Oxygenase MdpJ

Abstract: Tertiary alcohols, such as tert-butyl alcohol (TBA) and tert-amyl alcohol (TAA) and higher homologues, are only slowly degraded microbially. The conversion of TBA seems to proceed via hydroxylation to 2-methylpropan-1,2-diol, which is further oxidized to 2-hydroxyisobutyric acid. By analogy, a branched pathway is expected for the degradation of TAA, as this molecule possesses several potential hydroxylation sites. In Aquincola tertiaricarbonis L108 and Methylibium petroleiphilum PM1, a likely candidate catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
(59 reference statements)
0
26
0
2
Order By: Relevance
“…In the same strain, the TAME and TAEE metabolite tert-amyl alcohol (TAA) is desaturated by MdpJK to the hemiterpene 2-methyl-3-buten-2-ol, which is isomerized to prenol, oxidized to 3-methylcrotonyl-CoA, and then degraded via the leucine pathway (16). Consequently, strain L108 is able to grow on all four fuel oxygenate ethers (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same strain, the TAME and TAEE metabolite tert-amyl alcohol (TAA) is desaturated by MdpJK to the hemiterpene 2-methyl-3-buten-2-ol, which is isomerized to prenol, oxidized to 3-methylcrotonyl-CoA, and then degraded via the leucine pathway (16). Consequently, strain L108 is able to grow on all four fuel oxygenate ethers (16,17).…”
mentioning
confidence: 99%
“…tert-Butyl alcohol (TBA) from MTBE and ETBE is degraded via hydroxylation to 2-methyl-1,2-propanediol by the monooxygenase MdpJK (12, 13) and undergoes further enzymatic oxidation to 2-hydroxyisobutyric acid, which is then activated by coenzyme A (CoA) and isomerized to the common metabolite 3-hydroxybutyryl-CoA by the cobalamin-dependent mutase HcmAB (14,15). In the same strain, the TAME and TAEE metabolite tert-amyl alcohol (TAA) is desaturated by MdpJK to the hemiterpene 2-methyl-3-buten-2-ol, which is isomerized to prenol, oxidized to 3-methylcrotonyl-CoA, and then degraded via the leucine pathway (16). Consequently, strain L108 is able to grow on all four fuel oxygenate ethers (16,17).…”
mentioning
confidence: 99%
“…This strain was present in both water and brown precipitate samples and was subjected to further molecular genetics analyses for the phenotype of floc formation, which may be related to the brown precipitates that occurred in the well and tap water and also a trait desirable for activated sludge-based wastewater treatment. The Aquincola strains are capable of degrading gasoline-related contaminants (3)(4)(5)(6) and therefore may have great potential in bioremediation because of their floc-forming capability. Recently, it was shown that Aquincola species were one of the predominant proteobacteria in a membrane bioreactor (MBR) treating antibiotics-containing wastewater (7).…”
mentioning
confidence: 99%
“…A TAME és a TAEE katabolikus útvonala TAA köztiterméken át vezet, melyből kevés oxigén jelenlétében számottevő mennyiségben β-és γ-izoamilén is képződik [125]. Elegendő oxigén mellett a TAA-ból az MdpJ deszaturáz aktivitása nyomán 2-metil-3-butén-2-ol keletkezik, mely prenol és prenal intermediereken keresztül 3-metilkrotonsavvá alakul, ami azután a leucin katabolikus útvonalába csatlakozhat be [126]. Lényeges különbség tehát, hogy a TBA metabolizmusával összehasonlítva TAA esetében az MdpJ nem hidroxilációs reakciót katalizál, továbbá a TAA-n történő növekedéshez az L108 nem igényel kobalamint, viszont biotinra szüksége van.…”
Section: áBra Az Etbe Metabolikus úTvonala a Rhodococcus Ruber Ifp 20unclassified
“…A PM1 esetében is megfigyelhető a TBA-ból és a TAAból illékony, telítetlen szénhidrogén melléktermékek (izobutilén, ill. izoamilének) képződése alacsony oxigénkoncentráció mellett az L108-nál bemutatott mechanizmus szerint, de itt lényegesen kisebb intenzitású a folyamat [125]. A két törzsnél az mdpJ gén esetében megfigyelhető nagyfokú azonosság (~97%), valamint a csaknem egyforma génkörnyezet alapján feltételezik, hogy a TAA metabolizmusa a PM1-ben szintén az L108-nál leírt útvonalon megy végbe, melyet alátámaszt az a tény, hogy a PM1 képes a 2-metil-3-butén-2-ol egyedüli szén-és energiaforrásként történő hasznosítására [126]. A 2-HIBA metabolizmusa a PM1-ben nagy valószínűség szerint szintén az L108-nál leírtak szerint játszódik le.…”
Section: áBra Az Etbe Metabolikus úTvonala a Rhodococcus Ruber Ifp 20unclassified